(untitled) (Citizenship in Action: Extension and Culture Magazine, 2024)
Pedagogical practices developed in penal establishments assume the function of re-socializing by articulating the appropriation of scientific knowledge with social life. Thus, this article intends to understand which pedagogical practices are used in the State Penitentiary of Maringá (PEM) for remission of sentence and the possibilities of these practices for the process of resocialization of people deprived of liberty. The results showed that the provision of school education and the remission of sentences through study are ways of guaranteeing the rights of people deprived of their liberty, committing themselves to combating the social vulnerability of the inmates. However, the pedagogical practices developed at PEM, intend to raise awareness and promote capacities that value individuality for collective participation, promoting the necessary humanization for the resocialization process.